Peanut (Arachis hypogaea) allergen powder-dnfp for the mitigation of allergic reactions to peanuts in children and adolescents. (4th March 2023) - Casale, Thomas B.; Irani, Anne-Marie
ABSTRACT: Introduction: Peanut allergy can result in severe, sometimes fatal hypersensitivity reactions that place a considerable burden on the lives of patients. This article reviews the first approved immunotherapy for the mitigation of allergic reactions following accidental peanut exposure, peanut ( Arachis hypogaea ) allergen powder-dnfp (PTAH; Palforzia®, Aimmune Therapeutics). Areas covered: This article highlights the unmet need for patients with peanut allergy, describes the therapeutic landscape, and reviews the development of and clinical data for PTAH. Expert opinion: PTAH offers a standardized preparation of peanut allergen, with a tolerability and efficacy profile clearly defined through its robust clinical development and trial program. In children 4–17 years old, PTAH provides a standardized, approved product that many clinicians sought prior to initiating oral immunotherapy. PTAH reduced the likelihood of more severe reactions following exposure to peanut protein; although peanut avoidance remains essential, PTAH will enable more individuals with peanut allergy to participate in activities of daily life with less anxiety. Plain Language Summary: Peanut allergy is a serious, potentially fatal condition. It often starts in childhood, and the only treatment used to be emergency medicine after contact with peanuts. Children are recommended to avoid any contact with peanuts or products made with peanuts, which can be difficult and stressful, especially in social situations such as school. A treatment called oral immunotherapy, based on very small amounts of protein from peanut, was developed to help the body get used to coming into contact with peanuts without a dangerous reaction. PTAH (Peanut [ Arachis hypogaea ] allergen powder-dnfp) is a type of oral immunotherapy that doctors can prescribe for children with peanut allergy. It is the first medicine of its kind to be allowed and is prepared specially to make sure that the right amount of peanut is given to children. In controlled tests, children with peanut allergy were given increasing amounts of peanut to see how much they could eat before they had a bad reaction. Children who had been given PTAH for a few months could eat more peanut (without a bad reaction) than children who had been given a placebo. Although there are some side effects from PTAH, particularly tummy upsets, most children who took it in the trials were able to keep taking it. Although children with peanut allergy will still need to avoid peanuts, PTAH may allow them to lead a more normal life with less worry about accidentally coming into contact with peanuts.